Strengthening 21st Century Education Competencies in Indonesian Schools through an International Workshop - Sabariah; Hartono; Rufi'i; Nurmida Catherine Sitompul; Adi Bandono; Anidah Binti Robani; Nasaruddin Bin Rahmat (Universitas Veteran Bangun Nusantara, 2026)
The rapid development of digital technology and the demands of Society 5.0 have created both challenges and opportunities for 21st-century education in Indonesian schools. This community service activity aimed to enhance participants’ understanding of 21st-century education and strengthen their digital literacy and 4C skills through an international workshop involving collaboration between Indonesia and Malaysia. The program was implemented using a collaborative and participatory approach, including needs identification, training on 21st-century skills and digital literacy, interactive discussions, and evaluation of learning outcomes. The activity involved teachers and educational participants from Indonesia and Malaysia at MARA Junior Science College (MRSM), Malaysia. The results showed a significant improvement in participants’ understanding and attitudes toward 21st-century learning. Approximately 85% of participants reported increased awareness of critical thinking skills, 80% found the materials relevant to classroom practice, 78% demonstrated better understanding of Society 5.0 literacy, and 90% felt more prepared to face technological developments. In addition, 85% of participants were more motivated to integrate technology creatively into their teaching practices. This activity is expected to contribute to the sustainable improvement of 21st-century education implementation in schools through strengthened teacher competencies, increased digital literacy, and enhanced international collaboration in education.